Fifteenth General Review of Quotas-Notification from the Executive Board to the Board of Governors : 43739. (Policy Papers; Policy Paper ;, 2020)
On October 15, 2019, the Executive Board notified the Board of Governors that the conclusion of the Fifteenth Review was part of a package on Fund resources and governance reform on which discussions were still ongoing, and that it would report to the Board of Governors by November 2019 on the outcome of discussions on the Fifteenth Review, the goals and timetable for the Sixteenth Review, and on the way forward on IMF resources.